PENGARUH METODE ROLE PLAYING DALAM MENGATASI BULLYING TERHADAP MINAT BELAJAR PJOK SISWA KELAS IV SDN 165 PALEMBANG - Ayu Wandira; Endie Riyoko; Endang Surtiyoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Role Playing method in addressing Bullying on students' interest in learning Physical Education (PJOK) among fourth-grade students at SDN 165 Palembang. The research method used was a Quasi-Experimental Design with a Nonequivalent Control Group design. The population in this study consisted of all fourth-grade students at SDN 165 Palembang. The sampling technique used was random sampling, resulting in class IV A as the experimental group and class IV B as the control group. Data collection techniques in this study included validated Bullying and PJOK learning interest questionnaires. Based on the hypothesis test results, the obtained t-values were 3.426 and 3.043, while the critical t-value (t-table) was 2.011. Since the t-values were greater than the critical t-value (t > t-table), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that there is a significant effect of the Role Playing method in addressing Bullying on students' interest in learning PJOK among fourth-grade students at SDN 165 Palembang.